Influence of perceived parental views of failure on academic resilience among middle school students: a moderated mediation model - He, Wenying; Shi, Dasheng (Frontiers in Psychology, 2025)
Focusing on a sample of middle school students, this study examined the impact of perceived parental views of failure on academic resilience, as well as the mediating role of growth mindset and the moderating role of parental involvement in education. A total of 2,546 Chinese middle school students were recruited from the Beijing, Fujian, and Guizhou regions to complete a questionnaire. The data were analyzed using structural equation modeling (SEM) in SPSS 26.0 and PROCESS. The results indicate that perceived parental positive views of failure significantly and positively predict academic resilience, and this relationship is mediated by growth mindset. Furthermore, parental involvement in education moderates the direct effect within the mediation model. Interestingly, this effect is stronger at high levels of parental involvement in education but is not evident at low levels. Additionally, the moderating effects of specific dimensions of parental involvement in education (emotional, cognitive, and behavioral involvement) differ. Emotional involvement demonstrates the strongest moderating influence, while behavioral involvement shows the weakest. These findings provide theoretical insights and empirical support for developing intervention strategies aimed at enhancing the academic resilience of middle school students through family education.